Natural and anthropogenic evolution of the phosphate fund for soils in Ukraine - Nosko, B.S. (AgroChemistry and Soil Science, 2018)
The article summarizes the long term research results in the field stationary experiments and the results of nine tours of large-scale agro-chemical survey of soils in Ukraine regarding the determination of the essence of the formation of phosphate fund of soils, knowledge of the regularities, velocities and directions of its agro-evolution and the peculiarities of the formation of the phosphate profile of fertilized arable soils. It is revealed that the importance of forming a phosphate fund is the ratio of the content of soil organic carbon and the content of organic phosphates. It is noted that the lower the ratio Corg:Porg and higher the pH value of the soil solution, the less resistant are organophosphorus compounds. And vice versa, in a broad ratio more stable difficult hydrolyzed compounds are formed. In the most widespread soils of the Forest-Steppe and Steppe zones, the organic phosphate content ranges from 31 to 63 mg of P2O5 per 100 g of soil, increasing from 26 to 62 % of total phosphorus in the following sequence of soils: gray forest - dark gray podzolized – chernozem podzolized – chernozem ordinary - chernozem typical. It is proved that the content of organic phosphates in soils directly depends on the content of humus (r = 0.979). In chernozem typical (70- years fallow land) their number is reduced from 62,9 mg P2O5 per 100 g of soil in a layer of 0-20 cm to 27,8 mg in a layer of 140-160 cm. Corg:Porg value decreases with depth even more significantly, that is, the content of humus decreases more intensively than the content of organic phosphates. In chernozem typical heavy-loam in the field experiment of the NSC ISSAR O.N. Sokolovsky after the plowing of a 40-year-fallow land feather in an arable layer of soil on a control plot for 30 years of systematic plowing, the greatest changes were observed in the content of organic phosphates. The amount of phosphates decreased from 62,2 to 38,8 mg P2O5 per 100 g of soil. Also, the amount of active phosphates decreased from 35,1 to 23,7 mg P2O5 per 100 g of soil, but the content of mobile forms of phosphates (according to Chirikov and Olsen) remained virtually unchanged, which explains the high buffer of chernozem. The conclusion of the results of nine tours of agrochemical survey of soils showed a positive trend of growth of the average weighted content of mobile phosphate forms. During 1964-1970 (first tour) to 2006-2010 (ninth tour), it has increased on average in Ukraine from 71 to 112 mg P2O5, in Polissya - from 63 to 118, in the Forest-Steppe - from 81 to 106 and in the Steppe - from 67 to 120 mg P2O5 per kilogram of soil. The final part of the article lists the 11 most relevant research areas concerning phosphorus in soils of modern agroecosystems, whose results could provide favorable conditions for solving the problem of phosphorus nutrition of plants in national agriculture.